Pengaruh Edukasi Kesehatan Tentang Inovasi Biduran (Bidan Dan Dukun Kemitraan) Terhadap Minat Ibu Bersalin Ke Fasilitas Kesehatan Di Puskesmas Cimanggu Kabupaten Pandeglang Banten Tahun 2022: The Effect of Health Education on Biduran Innovations (Midwives and Partnership Shamans) on the Interests of Mothers Giving Birth to Health Facilities at the Cimanggu Health Center, Pandeglang Regency, Banten in 2022 - Ulfah, Fina (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: Maternal mortality is closely related to birth attendants, in some areas, the presence of traditional birth attendants as confidants in assisting childbirth. The Cimanggu Health Center in Pandeglang Regency 2017 has been doing Biduran innovation. One of the efforts to increase the interest of pregnant women to give birth in health facilities is by providing health education through the right media, including leaflets. The purpose of the study was to determine the effect of health education on midwife innovation (midwives and traditional birth attendants) on maternal interest in giving birth at health facilities at the Cimanggu Health Center, Pandeglang Regency Banten in 2022. Methods: The research method is a quasi-experimental design with a one-group pre-test-post-test design, the number of samples is 40 respondents, and the sampling technique is total sampling. The research instrument used a questionnaire. The data is primary data analyzed using the paired sample test, which was previously tested for normality Results: The results of the research on maternal interest in giving birth to health facilities before being given health education through leaflet media about hives innovation were mostly in the medium category as much as 55,0% after that with the high category as much as 60,0%. Breast milk production in breastfeeding mothers before giving mung bean juice was found to increase by 70,0%, and after that, it increased to 100%. The results of the bivariate analysis showed that there was an effect of health education on Biduran innovation on maternal interest in giving birth to health facilities with a p-value of 0,000. Discussion: The conclusion of health education about the innovation of hives has an effect on the interest of mothers in giving birth to health facilities. Maternity mothers are expected after receiving health education about the innovation of hives to give birth in health facilities so that when abnormalities are found during delivery, immediate action can be taken because the available facilities are more complete compared to giving birth at home.